Asymptomatic Bacteriuria in Women with Infertility - Hary Tjahjanto; Gabriele Emi Badia (Indonesian Socety of Obstetrics and Gynecology, 2026)
BACKGROUND: This study aims to determine the proportion/incidence of asymptomatic bacteriuria in women with infertility and calculate the proportion of asymptomatic bacteriuria in infertile women. METHODS: The study was conducted at Dr. RSUP. Kariadi, Semarang, in April 2021 - July 2021 by taking data on infertile female patients at the Dr. Central General Hospital. Kariadi in 2018-2020 underwent routine urine examinations. The design of this research method uses descriptive-analytic research with a cross-sectional approach. RESULTS: There were 137 women with infertility, 88 women in the primary infertility group and 49 women in the secondary infertility group. 110 (80.3%) women with the lowest level of bacteriuria were 107/uL and the highest level was 13,768/uL. Of 88 women with primary infertility, 70 (79.55%) women had asymptomatic bacteriuria and of 49 women with secondary infertility, 40 (81.63%) women had asymptomatic bacteriuria. The proportion of asymptomatic bacteriuria between the primary and secondary infertility groups was different, but not significant (p=0.76). CONCLUSION: The incidence of bacteriuria in infertile women is high and there is no difference in the proportion of asymptomatic bacteriuria in women with primary and secondary infertility. Keywords: Infertility, asimptomatic bacteriuria